Visual Function Tests as cost Effective Screening Tools For Diabetic Retinopathy - Ahmed, Faryal; Malik, Faraz Iftikhar; Azmat, Chaudhary Ehtsham; Gul, Ambreen; Raza, Ali (Pakistan Journal of Ophthalmology, 2020)
Purpose: To find out the importance of visual function tests as cost effective screening tools for diabetic retinopathy. Study Design: Descriptive, Cross sectional study. Place and Duration of Study: Ophthalmology Unit of Holy Family Hospital, from September 2018 to November 2018. Material and Methods: Two hundred and forty-two patients were selected by convenience sampling technique and were divided into three groups. Two groups of diabetics with and without retinopathy and one group of non-diabetics age-matched controls. After relevant history, patients were examined for Visual acuity, Color vision and Contrast sensitivity using Snellen’s Chart, 24 Plates Ishihara Chart and Pelli Robson Chart respectively. Staging of retinopathy was done after mydriasis. Results: Diabetic patients irrespective of type and stage, when compared with non-diabetic patients had a greater percentage of abnormal visual function tests. A 6/6 visual acuity was observed in 38.2% of non diabetics as compared to only 8.6% diabetics without retinopathy and 7.5% of diabetics with retinopathy. Color vision abnormalities were detected in only 8.6% of non diabetic patients. However, 11.1% of diabetics without retinopathy and 23.7% with retinopathy showed abnormalities of color vision. The percentage of abnormal Contrast sensitivity was 76.2% for diabetics with retinopathy and 60.4% for diabetics without retinopathy and 27.1% for non-diabetic patients. Conclusion: Evaluation of Visual Acuity, Color Vision and Contrast Sensitivity are cheap and easy tests that can be used to screen for diabetic retinopathy thereby allowing early interventions to prevent development of serious ocular diabetic complications.